INTERACTIVE TECHNOLOGIES: DIDACTIC CONDITIONS APPLICATIONS FOR TRAINING FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the problems of introduction of interactive technologies into the educational process. The attempt to substantiate the system of didactic conditions of interactive technologies effective use in future teachers ’ training has been made.